Reactions of All Escherichia coli Lytic Transglycosylases with Bacterial Cell Wall - Lee, Mijoon (2013)
The reactions of all seven Escherichia coli lytic transglycosylases with purified bacterial sacculus are characterized in a quantitative manner. These reactions, which initiate recycling of the bacterial cell wall, exhibit significant redundancy in the activities of these enzymes along with some complementarity. These discoveries underscore the importance of the functions of these enzymes for recycling of the cell wall.